Breakdown of the superplastic deformation behavior of heterogeneous nanomaterials at small length scales. Issue 1 (2nd January 2021) - Feldner, Patrick; Merle, Benoit; Göken, Mathias
Abstract : Ultrafine-grained and nanocrystalline materials frequently show an enhanced rate sensitivity of their mechanical behavior, which is generally assumed to be the consequence of interface sliding or thermally activated dislocation processes at the boundaries. Although this has been well documented on many different materials, the underlying mechanisms and their effect on the ductility of the material are still not well understood. Therefore, here, the deformation behavior of the ultrafine-grained, heterogeneous superplastic alloy Zn-22% Al was analyzed by small-scale nanoindentation and micropillar testing. The results show a breakdown of the superplastic deformation behavior in terms of a reduced strain rate sensitivity at small scales, which has not been reported before, although grain boundary sliding is still prevalent at the nanoscale. These results suggest that grain boundary sliding does not necessarily result in a high strain rate sensitivity and high ductility. Instead, a pronounced strain rate dependent flow behavior requires grain boundary sliding to be controlled by dislocation creep. IMPACT STATEMENT Superplastic flow is shown to persist down to a small material volume corresponding to a few grains. This has far-reaching consequences for the production of small-scale devices with complex geometries by superplastic forming. GRAPHICAL ABSTRACT: UF0001